THE MONUMENTALITY OF MODERN ARCHITECTURE AS OBSERVED IN JAKARTA’S POLA BUILDING - Lo Angela Irena ; Bachtiar Fauzy (Riset Arsitektur (RISA), 2018)
Abstract- After the Indonesian people declared Independence on 17 August 1945, Ir. Soekarno had a modern vision and mission, namely that architecture could become a symbol of strength and power in a state. Therefore, various monumental building projects emerged, especially in Indonesia’s capital Jakarta. One of these was the Pola building in Jakarta, a work of architecture designed by F. Silaban. The Pola building was actually constructed on top of Ir. Soekarno’s former house and functioned as an exhibition space to display Overall Projects Planned for the First Eight Years 1961-1969 (PSBPTP). The purpose of this study is to find out more about the architectural monumentality encountered in this research, to examine the concrete shape of the expression of this monumentality in the Pola building, and to determine the geometric elements, supporting the creation of this expression in this particular building. The research methods consist of the descriptive method, the analytical method and the interpretative method through the analysis of the physical and spatial data related to the observation of the building activities; interviews held with the building manager and the study made of the background literature on the object of study. The theory concerning architectural monumentality, the theory dealing with principles of arrangement (lay-out), the theory of geometrical elements and finally the theory concerning archetypes have been used to analyze the physical construction data regarding their monumentality. The conclusion that may be drawn from this research is that the monumentality observed in the Pola building can be gleaned from the geometrical elements shaped like a striped rectangle as the composing element that contributes to its monumentality with its repetitive lay-out showing a static and balanced rhythm. The benefit of this research lies in the hope that it may make a positive contribution to the development of scientific knowledge in the field of architecture., and especially modern architecture in whose field this research has focused on the monumentality of buildings designed in the modern architectural style based on the physical condition of the building in question. Keywords : Monumentalism, Architecture, Modern